2022
DOI: 10.3390/v14081717
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviral 2B Interacts with VDAC3 to Regulate Reactive Oxygen Species Generation That Is Essential to Viral Replication

Abstract: Enterovirus (EV) 71 caused episodes of outbreaks in China and Southeast Asia during the last few decades. We have previously reported that EV71 induces reactive oxygen species (ROS). However, the underlying mechanism remains elusive. Co-immunoprecipitation-proteomic analysis revealed that enteroviral 2B protein interacted with mitochondrial voltage-dependent anion channel 3 (VDAC3). Knockdown (KD) of VDAC3 expression specifically inhibited enteroviral replication. Single-round viral replication was also inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…37 VDAC3 interaction was found to be associated with a reduction in the synthesis of hypotaurine, an important endogenous antioxidant that plays a role in maintaining the homoeostasis of ROS levels. 38 Fourth, VDAC can interact with or promote the activation of other proteins to reduce the apoptosis of infected cells. It was confirmed that VDAC2 promotes apoptosis of IBDV-infected cells when triggered by IBDV protein VP5 39 ; however, when receptor of activated protein C kinase 1 (RACK1) forms a complex with VP5 and VDAC2, apoptosis is inhibited.…”
Section: Vdac-dependent Mechanisms That Enhance Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 VDAC3 interaction was found to be associated with a reduction in the synthesis of hypotaurine, an important endogenous antioxidant that plays a role in maintaining the homoeostasis of ROS levels. 38 Fourth, VDAC can interact with or promote the activation of other proteins to reduce the apoptosis of infected cells. It was confirmed that VDAC2 promotes apoptosis of IBDV-infected cells when triggered by IBDV protein VP5 39 ; however, when receptor of activated protein C kinase 1 (RACK1) forms a complex with VP5 and VDAC2, apoptosis is inhibited.…”
Section: Vdac-dependent Mechanisms That Enhance Viral Infectionmentioning
confidence: 99%
“…32 Additionally, in an experiment on EV71-infected cells in which VDAC3 was knocked down, both titre and genomic RNA levels were significantly reduced. 38 Moreover, a study on LCDV infection and the possible role of the VDAC2/RACK1 complex in viral entry and replication revealed that knocking down the VDAC2/RACK1 complex resulted in lower LCDV copy numbers and viral load in LCDVinfected FG cells, shedding light on the importance of this complex to promote viral entry. 31 According to the study by Sheng and colleagues, viral entry was mediated by the caveolae-dependent endocytic pathway, which can potentially be targeted to prevent viral entry.…”
Section: Viral Infection Inhibition By Downregulation Of Vdacmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide anion production was determined by MitoSOX Red staining and flow cytometry as previously described [50]. The mitochondrial mass and mitochondrial membrane potential were determined, respectively, by staining with MitoTracker Green and JC-1 and performing cytometric analyses as previously described [51,52].…”
Section: Oxygen Consumption Rate (Ocr) and Extracellular Acidificatio...mentioning
confidence: 99%
“…EV71 infection also leads to increased ROS generation, accompanied by decreased levels of antioxidants (taurine and hypotaurine) [9]. It was shown, that enteroviral 2B protein interacts with mitochondrial voltage-dependent anion channel 3 (VDAC3) -one of the pore-forming protein localized to the outer membrane of mitochondria, and this interaction is essential to mitochondrial ROS generation and viral replication [10]. It is described that oxidative stress elicited by viruses can promote inflammation and subsequent tissue destruction [30,19].…”
Section: Figure 7 1a Inhibits Early and Middle Stages Of Coxsackievir...mentioning
confidence: 99%